STUDY ON CONSUMER ACCEPTANCE OF JELLY CANDY Seaweed (Eucheuma cottonii) WITH THE ADDITION OF NATURAL DYES rosele (Hibiscus sabdariffa L) - Yuliati '; N. Ira Sari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aims to determine consumer acceptance of jelly seaweed (Eucheuma cottonii) with the addition of natural dyes rosele (Hibiscus sabdariffa L). The method used is experiment with a completely randomized design, consisting of 4 levels of treatment of R0 (without the addition of roselle), R1 (extra rosela 15%), R2 (extra rosela 20%), and R3 (extra rosela 25%). The parameters tested were organoleptic, chemical analysis and treatment of the best views of the parameters tested is treated R3 (xtra rosela 25%) with a red color such criteria (7.29), the distinctive aroma of seaweed no (7.46), sweetness and typical rosela acid (7.57), teksturserat-fiber smooth and not sticky (7.58), with a water content of 15.20%, ash content of 0.42%, 4.33% reducing sugar.Keywords: jelly, roselle, seaweed, organoleptic assessment